Simultaneous Quantification and Visualization of Titanium Dioxide Nanomaterial Uptake at the Single Cell Level in an In Vitro Model of the Human Small Intestine. Issue 5 (21st March 2019) - Meyer, Thomas; Venus, Tom; Sieg, Holger; Böhmert, Linda; Kunz, Birgitta M.; Krause, Benjamin; Jalili, Pegah; Hogeveen, Kevin; Chevance, Soizic; Gauffre, Fabienne; Burel, Agnes; Jungnickel, Harald; et al.
Abstract: Useful properties render titanium dioxide nanomaterials (NMs) to be one of the most commonly used NMs worldwide. TiO2 powder is used as food additives (E171), which may contain up to 36% nanoparticles. Consequently, humans could be exposed to comparatively high amounts of NMs that may induce adverse effects of chronic exposure conditions. Visualization and quantification of cellular NM uptake as well as their interactions with biomolecules within cells are key issues regarding risk assessment. Advanced quantitative imaging tools for NM detection within biological environments are therefore required. A combination of the label‐free spatially resolved dosimetric tools, microresolved particle induced X‐ray emission and Rutherford backscattering, together with high resolution imaging techniques, such as time‐of‐flight secondary ion mass spectrometry and transmission electron microscopy, are applied to visualize the cellular translocation pattern of TiO2 NMs and to quantify the NM‐load, cellular major, and trace elements in differentiated Caco‐2 cells as a function of their surface properties at the single cell level. Internalized NMs are not only able to impair the cellular homeostasis by themselves, but also to induce an intracellular redistribution of metabolically relevant elements such as phosphorus, sulfur, iron, and copper. Abstract : State‐of‐the‐art label‐free visualization and quantification methods are applied to investigate nanomaterials in biological environment at sub‐cellular resolution. 3D translocation patterns of titanium dioxide nanomaterials in Caco‐2 cells are visualized and quantified. Cellular homeostasis of minor and trace elements is evaluated under the influence of nanomaterials. Colocalization of intrinsic elements with nanomaterials is quantified within single cells.